Analisis Natrium Siklamat dalam Minuman Es Teh Menggunakan Metode HPLC: Hasil Pengembangan dan Validasi - Wira Ayuriza; Budhi Oktavia (MASALIQ, 2026)
The high consumption of iced tea beverages in the community increases potential exposure to artificial sweeteners, particularly sodium cyclamate, whose use is regulated in Regulation of the National Agency of Drug and Food Control (BPOM) No. 11 of 2019. The use of cyclamate that does not comply with regulatory limits may pose health risks, thereby requiring effective monitoring through analytical laboratory methods that are accurate, precise, and validated. BPOM has established a standard method for the determination of sodium cyclamate using high performance liquid chromatography (HPLC); however, in practice there are still variations in HPLC operating conditions across laboratories, such as differences in column type, mobile phase composition, and detection parameters, which may affect analytical results. Therefore, this study aimed to develop and validate an HPLC method that is compatible with specific laboratory conditions while still meeting analytical performance requirements. The results showed that a new HPLC method was successfully developed and validated for the analysis of sodium cyclamate levels in iced tea beverages. This method met all validation parameters, including linearity, precision, accuracy, limit of detection (LOD), and limit of quantitation (LOQ), and is thus suitable for determining sodium cyclamate content. The use of a methanol–water mobile phase with a 5:95 ratio proved optimal, as it provided good separation efficiency, adequate analysis time, and simplified the testing procedure. Overall, the developed method offers a practical, economical, and reliable analytical alternative to support food safety surveillance related to the use of artificial sweeteners in iced tea beverages.